2005
DOI: 10.1128/jcm.43.12.6183-6185.2005
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cellular Human Immunodeficiency Virus DNA Level and Immunological Parameters in Patients with Undetectable Plasma Viremia Level during Highly Active Antiretroviral Therapy

Abstract: The association between human immunodeficiency virus (HIV) DNA load and immunologic parameters was investigated in 163 HIV-infected patients with undetectable plasma viremia during highly active antiretroviral therapy (HAART). Patients with HIV DNA below the 25th percentile (133 copies/10 6 peripheral blood mononuclear cells) had higher pre-HAART (P ‫؍‬ 0.001) and current (P ‫؍‬ 0.005) CD4 counts and a prolonged duration of treatment (P ‫؍‬ 0.001). At adjusted analysis, prolonged duration of treatment was inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Low levels of ongoing, persistent HIV replication may contribute to the longevity of the latent viral reservoir by continually fuelling new rounds of infection in resting CD4 + T cells. The quantification of HIV DNA in peripheral blood cells, in addition to RNA viral load in patients' plasma, may be extremely important for disease monitoring, especially in HAART-treated patients [23,27,[37][38][39], when RNA viral load is undetectable by current techniques [25,30,40,41]. This report studied total and 2-LTR circular HIV-1 DNA proviral load, by SYBR Green-based real-time PCR, a useful and reliable approach for determining genome regions with a high mutation rate [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of ongoing, persistent HIV replication may contribute to the longevity of the latent viral reservoir by continually fuelling new rounds of infection in resting CD4 + T cells. The quantification of HIV DNA in peripheral blood cells, in addition to RNA viral load in patients' plasma, may be extremely important for disease monitoring, especially in HAART-treated patients [23,27,[37][38][39], when RNA viral load is undetectable by current techniques [25,30,40,41]. This report studied total and 2-LTR circular HIV-1 DNA proviral load, by SYBR Green-based real-time PCR, a useful and reliable approach for determining genome regions with a high mutation rate [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…A lower HIV DNA load after a defined duration of HAART was significantly related to a higher pre-HAART CD4 cell count and percentage and a prolonged duration of antiretroviral treatment (2,19,27,30). Furthermore, the absence of previous exposure to antiretroviral therapy was a predictive factor for larger decreases in cellular HIV-1 DNA levels (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a lower HIV DNA load during cART is associated with better immune recovery (194,200,201). Similarly, a low HIV DNA load was found to be predictive of better immune restora-tion in children on cART (202) and was associated with CD4 cell count dynamics during cART combined with interleukin-2 (203).…”
Section: Total Hiv Dna Load During Cart Is Informative Of Patient Prementioning
confidence: 98%
“…Multivariate analysis indicated that low HIV DNA load in patients with cART for a median of 25 months was significantly associated with prolonged HIV RNA suppression on cART (194). HIV DNA load during cART was independently associated with cumulative HIV RNA viremia over the previous 5 years ( 93,192).…”
Section: Total Hiv Dna Load During Cart Is Informative Of Patient Prementioning
confidence: 99%